(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article deals with the plot-compositional structure of the plays of the 30s of the XX century. The dramaturgy of this period bears all the hallmarks of a new European drama. The depiction of historical events is combined in them with in-depth attention to the inner world of a person; acute social and moral problems destroy the usual stereotypes of family and everyday drama. The voice of the author sounds in the works simultaneously with the voice of history, creating a carefully hidden background.